Fibonacci-Like Polynomials and Some Properties - Bhatnagar, Shikha; Singh, Bijendra; Sikhwal, Omprakash (International Journal of Advanced Mathematical Sciences, 2013)
The Fibonacci and generalized Fibonacci polynomials are famous for possessing wonderful and amazing properties and identities. In this paper, we introduce Fibonacci-Like polynomials (FLP) and describe some properties. We obtain few properties by defined Fibonacci-Like polynomials - matrix. Further we establish few identities like Catalan’s, Cassini’s, d’Ocagne’s  through Binet’s formula and few identities  by using explicit summation formula which are related to hypergeometric functions of FLP.